Penilaian Cadangan Karbon Cagar Alam dan Taman Wisata Alam Talaga Warna sebagai Indikator Ketahanan Ekosistem - Wulan Tresna Mukti; Susanti Withaningsih; Asep Pranajaya; Dhimas Pranowojati; Virni Budi Arifanti (Jurnal Ilmu Kehutanan, 2026)
Global climate change underscores the need for nature-based mitigation to reinforce ecosystem resilience. Therefore, this research aimed to examine carbon stocks in Talaga Warna, West Java,and evaluate their potential as an indicator of ecosystem resilience. Data were obtained from three transects and six permanent plots using allometric equations to estimate tree biomass and carbon stocks. Vegetation was classified into functional groups, while species diversity and evenness were assessed using the Shannon-Wiener diversity index(H′) and Pielou's evenness index(J). The results showed that carbon stocks varied across transects and plots, with an average of 192.77tC/ha. Canopy trees accounted for the largest share of total carbon, while other vegetation groups played smaller but significant roles. Plots with higher H′ and J values showed more balanced carbon distribution. Based on observations, plots dominated by large species stored more carbon despite lower diversity. Correlation analysis presented a weak 2 positive relationship (R =0.024) between species diversity and total carbon. This suggested that stand structure and the dominance of high-biomass species had a stronger influence than diversity alone. In conclusion, carbon stock had potential as a practical indicator of ecosystem resilience, reflecting the balance among stand structure, vegetation diversity, and ecological function in the montane forest.